FARMERS KNOWLEDGE, ATTITUDE AND PRACTICES (KAP) TOWARDS RODENT PEST MANAGEMENT IN RICE - ANUSHA, B.; RAO, N. SRINIVASA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
A survey on Knowledge, Attitude and practice (KAP) on rodent pest management was carried out during the year 2021-22 in West Godavari district of Andhra Pradesh through a structured questionnaire to know about the level of Knowledge, their Attitude and Practices followed by them in controlling the rodents. The data revealed that 23.6% of the farmers have low level of knowledge, 41.6% of the farmers have moderate level of knowledge and 34.8% of the farmers have high level of knowledge with regard to rodent pest management. Regarding the attitude of farmers towards rodent pest management 36.3% of the farmers comes under Primary adopters category which requires training programmes as their motivational media, 51.2% under secondary adopters category, 12.5% of the farmers were considered as Laggards. From the overall response towards practicing the rodent management options, 31.8% of the farmers have low level of skills and practices, 25.2% of the farmers have medium level of skills and practice whereas 43.11% of the farmers have high level of skills and practice with regard to rodent pest management. This type of study helps in developing and designing integrated rodent management strategies.